EFEKTIVITAS PENDEKATAN SAINTIFIK BERBASIS GROUP INVESTIGATION DAN DISCOVERY LEARNING DITINJAU DARI MINAT BELAJAR MAHASISWA - Ira Vahlia; Yeni Rahmawati; Tri Anjar (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
Appropriate learning models contribute to student learning interest in math. The purpose of this study is to describe the difference in effectiveness between scientific approach based on group investigation and discovery in terms of student's interest in learning. The research that is conducted is quasi experimental research and the design used is 2 x factorial description. In experimental class I that apply scientific approach model based on study group investigation obtained the average value of learning outcome of 66.60 while in the experimental class II applying the approach Science-based discovery learning obtained the average value of posttest of 76.28. Based on the marginal rate, the scientific approach to discovery-based learning on moderate interest in learning outcomes is higher than the learning outcomes at high and low interest. In the scientific approach based on group study investigation and discovery learning there are differences in average learning outcomes between high, medium and low interest. Scientific approach based on group investigation learning on higher interest in learning outcomes is higher than moderate and low interest.